High level of soluble tumor necrosis factor receptors is associated with lower residual diuresis volume in patients on hemodialysis: An exploratory study - Gabriele Teixeira Gonçalves; Luciana Martins de Mello Santos; Pedro Henrique Scheidt Figueiredo; Jaqueline de Paula Chaves Freitas; Jousielle Márcia Santos; Joyce Noelly Vitor Santos; Fidelis Antônio da Silva Junior; Frederico Lopes Alves; Vanessa Gomes Brandão; Emílio Henrique Barroso Maciel; Maria Cecília S. M. Prates; Borja Sañudo; et al. (PLoS ONE, 2025)
Objective Patients on hemodialysis commonly present with elevated inflammatory markers. It is noteworthy, however, that higher levels of these markers may deteriorate residual renal function in in these individuals. Further investigation is essential to clarify the potential link between systemic chronic inflammatory parameters and residual diuresis volume in this population, particularly when accounting for confounding variables such as body composition. This study aimed to explore the possible relationship between inflammatory parameters and residual diuresis volume in patients on hemodialysis. Methods Blood samples were collected from patients on hemodialysis for the analysis of soluble receptors: 1) tumor necrosis factor receptor 1 (sTNFR1), 2) tumor necrosis factor receptor 2 (sTNFR2), and 3) leptin. Confounding variables, such as gender, age, duration of hemodialysis, Kt/V (a measure of dialysis adequacy), and body composition assessed using the dual-energy X-ray absorptiometry (DXA), were also evaluated. Data analyses were conducted using both single and multiple regression models, adjusted for the confounding parameters. Results Of the total sixty participants, 27 (45%) were classified as anuric, and 33 (55%) as non-anuric. High sTNFR1 plasma levels were associated with a lower residual diuresis volume, irrespective of adjustments for confounding parameters (R² = 25.4%; β = 0.504; p < 0.001). Conclusion This study supports the hypothesis that higher systemic levels of sTNFR1 may deteriorate residual renal function, as evidenced by the lower residual diuresis volume observed in patients on hemodialysis. These findings suggest that interventions aimed at reducing systemic inflammation may be beneficial in preserving residual renal function and improving clinical outcomes in these patients. Chronic Kidney Disease (CKD) is characterized by any persistent alteration or abnormality in kidney structure or function lasting over ninety days [1]. CKD’s subtle onset complicates diagnosis, and once established, it often progresses irreversibly [2]. Recognized globally as a major public health issue [3], CKD affects 10–13% of adults in economically advanced countries [1]. In Brazil, CKD poses significant healthcare challenges, causing over 35,000 deaths annually and incurring substantial treatment costs [4]. Projections indicate around 10 million CKD cases in Brazil, with about 90,000 individuals requiring dialysis [5,6]. This data underscores the urgent need to address CKD as a critical health challenge and develop comprehensive strategies to mitigate its impact on public health and healthcare costs.